Emerging elemental two-dimensional materials for energy applications. Issue 35 (2nd August 2021) - Wu, Zongxiao; Qi, Junlei; Wang, Wenbin; Zeng, Zhiyuan; He, Qiyuan
Abstract : Elemental two-dimensional (2D) materials possess distinct properties and superior performances across a multitude of fundamental and practical research fields. Abstract : Elemental two-dimensional (2D) materials possess distinct properties and superior performances across a multitude of fundamental and practical research fields. Although a tremendous number of earlier studies focus on graphene and its derivatives, other emerging elemental 2D materials, such as borophene, silicene, black phosphorene, antimonene, tellurene, bismuthene and arsenene, are attracting increasing research interest in electronics and optoelectronics, as well as various energy storage and conversion applications, owing to their unique structural, electrochemical and electronic properties. In particular, emerging elemental 2D materials often possess large surface areas, high theoretical capacity, structural anisotropicity, high carrier mobility and tunable bandgaps, making them promising candidates in many energy storage and conversion technologies. Recently, we have witnessed remarkable progress in the preparation, characterization, and application of many emerging elemental 2D materials. However, the challenging yet vastly different synthetic strategies and resulting physicochemical properties, along with complex theoretical and experimental results, make it difficult to navigate through their applications in specific research fields. In this perspective, we summarize the progress of emerging elemental 2D materials in terms of their preparation methods, properties and figures of merit in energy storage and catalytic applications. Furthermore, we present our insight into the challenges and opportunities, which would hopefully shed light on the great potential of this ever-expanding field.